Manejo respiratório em doenças neuromusculares: revisão de literatura - Lorine Uchoa Inácio Matos; Marcelo Fouad Rabahi (UniEVANGÉLICA, 2018)
Objective: To describe the respiratory involvement in neuromuscular diseases and treatments available for ventilatory support in such pathologies. Methods: Bibliographical survey of scientific articles searched in databases (Capes, Pubmed and SciELO) and articles / book chapters available at http://www.doctorbach.com. Results: 37 articles / chapters related to ventilatory failure in neuromuscular diseases and their management were selected and reviewed. Conclusion: There is evidence from the literature indicating the use of noninvasive ventilation in this group of patients, with the aim of improving gas exchange, relieving dyspnea, resting the inspiratory muscles, reducing the incidence of nosocomial infections, hospitalizations and mortality.